2006
DOI: 10.1158/0008-5472.can-05-4290
|View full text |Cite
|
Sign up to set email alerts
|

KRN951, a Highly Potent Inhibitor of Vascular Endothelial Growth Factor Receptor Tyrosine Kinases, Has Antitumor Activities and Affects Functional Vascular Properties

Abstract: Vascular endothelial growth factor (VEGF) plays a key role in tumor angiogenesis by stimulating the proangiogenic signaling of endothelial cells via activation of VEGF receptor (VEGFR) tyrosine kinases. Therefore, VEGFRs are an attractive therapeutic target for cancer treatment. In the present study, we show that a quinoline-urea derivative, KRN951, is a novel tyrosine kinase inhibitor for VEGFRs with antitumor angiogenesis and antigrowth activities. KRN951 potently inhibited VEGF-induced VEGFR-2 phosphorylati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
139
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(146 citation statements)
references
References 36 publications
7
139
0
Order By: Relevance
“…Furthermore, although the vascular casts presented clearly revealed the presence of transluminal pillars, the authors did not recognize the phenomenon of intussusceptive angiogenesis. Similar changes in vasculature have been observed in murine orthotopic B16/BL6 melanoma tumor model after treatment with either PTK/ZK (Rudin et al, 2005) or other tyrosine kinase inhibitors (Nakamura et al, 2004;Nakamura et al, 2006;Ruggeri et al, 2003). In each instance, the depicted changes in the vasculature corresponded to those associated with intussusception.…”
Section: B Asupporting
confidence: 58%
“…Furthermore, although the vascular casts presented clearly revealed the presence of transluminal pillars, the authors did not recognize the phenomenon of intussusceptive angiogenesis. Similar changes in vasculature have been observed in murine orthotopic B16/BL6 melanoma tumor model after treatment with either PTK/ZK (Rudin et al, 2005) or other tyrosine kinase inhibitors (Nakamura et al, 2004;Nakamura et al, 2006;Ruggeri et al, 2003). In each instance, the depicted changes in the vasculature corresponded to those associated with intussusception.…”
Section: B Asupporting
confidence: 58%
“…Anti-angiogenic agents such as anti-VEGF antibody and tyrosine kinase inhibitor were reported that decrease both K trans and IAUGC (O'Connor et al, 2007;Bradley et al, 2008;Bradley et al, 2009), and the decrease in K trans in solid tumours is concerned with the anti-tumour effect (Morgan et al, 2003;Marzola et al, 2004;Nakamura et al, 2006;Flaherty et al, 2008). In this study, K trans , IAUGC 60 , and v p were increased significantly 24 h after the A-83-01 treatment.…”
Section: Discussionmentioning
confidence: 57%
“…Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) is one of the evaluation methods of anti-angiogenic agents, such as anti-VEGF antibody and tyrosine kinase inhibitor, clinically (Morgan et al, 2003;O'Connor et al, 2007) and preclinically (Marzola et al, 2004;Nakamura et al, 2006;Bradley et al, 2009), by calculating pharmacokinetic parameters, including fractional plasma volume (v p ) and the volume transfer constant (K trans ) from the enhancement of tumour signal intensity by gadolinium (Gd) contrast agent (Tozer, 2003;Kiessling et al, 2007). To my knowledge, however, there are no reports to evaluate TbR-I inhibitor by DCE-MRI.…”
mentioning
confidence: 99%
“…In addition, nestin inhibits the growth of human primary cultured vascular endothelial cells in vitro. Thus, nestin may serve as a novel therapeutic target in PDAC angiogenesis similar to VEGFR inhibitors (58). Furthermore, expression of nestin in PDAC cells was detected in approximately 30% of PDAC cases (22).…”
Section: Discussionmentioning
confidence: 99%